Engineered biomimetic cisplatin-polyphenol nanocomplex for chemo-immunotherapy of glioblastoma by inducing pyroptosis - Xinyan Hao; Yucheng Tang; Wenjie Xu; Ming Wang; Jiayi Liu; Yongjiang Li; Jun He; Yanjin Peng; Pengcheng Sun; Dehua Liao; Xiongbin Hu; Tiantian Tang; et al. (Journal of Nanobiotechnology)
Abstract Glioblastoma multiforme (GBM) is characterized by pronounced immune escape and resistance to chemotherapy-induced apoptosis. Preliminary investigations revealed a marked overexpression of gasdermin E (GSDME) in GBM. Notably, cisplatin (CDDP) demonstrated a capacity of inducing pyroptosis by activating caspase-3 to cleave GSDME, coupled with the release of proinflammatory factors, indicating the potential as a viable approach of inducing anti-tumor immune activation. For the effective delivery of CDDP, the CDDP-polyphenol nanocomplexes were prepared, and catalase and copper ions were incorporated to fortify structural integrity, enhance glutathione (GSH) responsiveness, and ameliorate tumor hypoxia. Additionally, BV2 microglial cells were engineered to overexpress programmed death-1 (PD-1), and the membrane is employed for nanocomplex coating, effectively blocking the CDDP-induced upregulation of programmed death ligand 1 (PD-L1). Furthermore, the angiopep-2 peptide was modified to efficiently cross the blood brain barrier and specifically target GBM cells. In vitro analyses confirmed potent cytotoxicity and characteristic induction of pyroptosis. In vivo assays corroborated the enhancement of tumor targeting, culminating in an obvious suppression of tumor proliferation. A notable activation of immune cells was observed within tumors and lymph nodes, indicative of a synergistic effect of chemotherapy and immunotherapy, underscoring its potential as a safe and efficacious therapeutic strategy against GBM.